GRAMMATICAL MEANS EXPRESSING DIRECTIVE SPEECH ACTS IN ENGLISH - Alimova Nodira Komilovna; Pulatova Irodahon (CANADA - SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2025)
This article explores the grammatical means expressing directive speech acts in the English language. Directive speech acts, which include commands, requests, suggestions, and advice, are examined in terms of their syntactic structures and modal verb usage. The study focuses on how imperative forms, interrogative constructions, and modal auxiliaries such as can, could, should, and must function in the realization of directive intentions. By analyzing examples from both spoken and written English, the paper highlights the pragmatic implications of grammatical choices and the influence of context on directive force.